Reconfigurable antennas for GSM and WLAN applications - IHD Mavidu Nipunath Iddagoda (2013)
Design of a frequency reconfigurable antenna that could switch between GSM 900MHz and WLAN 2400 MHz is presented. The switchable antenna is realized in the form of GSM and WLAN patches. The design presents a novel nested patches structure with a proper slot width to isolate the two nested patches.